Clinical results of scarf osteotomy - Gluščević, Boris; Stanojković, Aleksandar; Bukumirić, Dragica; Jeremić, Danilo (Vojnosanitetski pregled, 2023)
Background/Aim. There are a few research papers in Serbia that report on the clinical results of scarf osteotomy (SO) and its long-term effects. The aim of this retrospective study was to evaluate the efficacy of SO in hallux valgus (HV) deformity correction, as well as the degree of recurrence and its possible causes. Methods. The study included 48 patients (52 feet) who underwent SO. The average follow-up time was 103.9 (63–156) months. In order to clinically evaluate the results, the American Orthopedic Foot and Ankle Society (AOFAS) scale and the Visual Analog Scale (VAS) of pain were used. In order to radiographically determine the degree of deformity, preoperative and postoperative radiographs of the feet were taken in the standing position, and the following parameters were determined: HV angle (HVA), intermetatarsal angle, distal metatarsal articular angle, and sesamoid position. Results. The AOFAS scores increased from 19 (5–45) points preoperatively to 92 (54–100) points at the time of the latest follow-up examination (p < 0.001). The VAS values significantly improved from 10 (8–10) preoperatively to 0 (0–6). The average HVA correction was 24.8°. The recurrence rate in patients in whom the HVA was greater than 20° was 26.9%. Conclusion. Although SO is a proven procedure for the correction of HV, long-term results still show a relatively high rate of recurrence.